Reducing Burnout among Police Personnel through Digital Competence, Stress Management, and Work Engagement - Renil Septiano; Asphari Wahyu Siregar (Dinasti Review, 2026)
This study examines the effects of digital competence, stress management, and police officer engagement on burnout among personnel at the Pesisir Selatan Police Resort. The study used a quantitative explanatory design with a survey approach. Data were collected from 138 personnel selected from 211 active members and analyzed using multiple linear regression with IBM SPSS 26. The results show that digital competence has a negative and significant effect on burnout. Stress management also has a negative and significant effect on burnout. Police officer engagement similarly has a negative and significant effect on burnout. Simultaneously, the three variables significantly affect burnout, with an R Square value of 0.745. These findings indicate that stronger digital capability, better stress management, and healthier engagement contribute to lower burnout among police personnel. The study confirms that personal resources play an important role in helping police officers cope with demanding work conditions. The findings imply that police organizations need to strengthen digital skills, provide stress management support, and maintain healthy engagement to reduce burnout and sustain organizational effectiveness.